Program Evaluation Challenges for Early-Career Extension Professionals: What Can You Do to Reduce the Stress? - John M. Diaz; Laura A. Sanagorski Warner (EDIS, 2019)
This article outlines meaningful strategies to overcome the program evaluation challenges that early-career Extension professionals face. The strategies outlined in this article are grounded in the experiences of Extension professionals in three states (Florida, North Carolina and Pennsylvania) and center on providing solutions to the challenges that newer Extension professionals felt were the most important to address, in order to provide a manageable framework for agents to use. This new five-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by John Diaz and Laura Warner. http://edis.ifas.ufl.edu/wc335